AB0671 DISCORDANCE IN ANTI-TIF-1γ ANTIBODIES DETECTION THROUGH COMMERCIAL KIT IN COMPARISON WITH HOMEMADE IMMUNOBLOT: CLINICAL EVALUATION. (June 2019) - Millán arciniegas, Ana Milena; Angeles Martinez, M.; Mariscal, Anais; Baucells, Andres; Alserawan, Leticia; Trallero, Ernesto; Díaz-Torné, Cesar; Laiz, Ana; Magallares, Berta; Moya, Patricia; Park, Hyesang; García-Guillén, Andrea; et al.
Abstract : Background: The antibody against the transcriptional intermediate factor 1γ (Anti-TIF1γ or anti-p155), is considered specific for dermatomyositis (DM) and its a marker of cancer risk. Our center carries out the determination of anti-TIF1γ by a homemade immunoblot (IB) technique with a 155 kDa TIF1γ human recombinant protein (OriGene). Currently there is a commercial technique of IB to detect TIF1γ (Euroimmun), however, commercial kits sometimes elaborate antigens without using whole protein structure. To date, there are no studies that study the agreement between the commercial kit and homemades IB. Objectives: 1-To compare the commercial IB results of anti-TIF1γ with homemade IB. 2-To describe and compare the clinical characteristics of the patients analyzed by both techniques. METHODS: Observational retrospective study that included adult patients with some determination of anti-TIF1γ antibodies since 2014 in two tertiary-level university hospitals. We collected demographic and clinical data of all patients. Taking into account their diagnoses we grouped them into: Cancer associated Myositis (CAM), DM without cancer, Systemic autoimmune Diseases (SAD) non-DM and other diagnoses. Subsequently, the clinical agreement with the IB results of anti-TIF1γ performed by commercial (cIB) and homemade (hIB) technique were analyzed. A p value < 0.05 was considered statistically significant. RESULTS: 48 patients were recruited (77.1% women). 13 had diagnosis of CAM, 19 of DM without cancer, 7 of other non-DM EAS, and 9 had other diagnoses. Of all DM (CAM and DM without cancer), 12 were positive for both techniques. 5 presented discordant results (4 hIB positive with negative cIB and 1 cIB positive with negative hIB). 15 DM were negative for the two techniques, of which 8/15 had other antibodies associated with autoimmune Myopathy (3 NXP-2, 1 Mi2, 1 MDA5, 1 SAE, 1 Jo1 and 1 Ro52). When we analyzed patients with CAM with both techniques, 10/13 presented positive hIB vs 8/13 cIB positive. DM without cancer, 6/19 had positive hIB vs 5/19 cIB positive. The sensitivity and specificity of each test was evaluated in CAM and DM without cancer, being 61.5% and 73.7% respectively for cIB (p = 0.071), compared to 76.9% and 68.4% for hIB (p = 0.029). In non-DM SAD group, 1 patient had positive determination for both techniques, 3 had positive cIB with negative hIB, and 3 cIB negative with positive hIB. We also found other antibodies in 6/7 patients with non-DM SAD. The 9 patients with other diagnoses were: 1 positive for both techniques and 8 positive for cIB and negative for hIB. CONCLUSIONS: Homemade IB with 155 kDa recombinant protein was superior to cIB to detect TIFγ in our serie of patients with CAM. This could have clinical implications in screening and early detection of neoplasia that affect false negative by cIB. A positive cIB in patients not suspected as a SAD were negative for hIB in the major part of cases. It would be recommended to check the commercial IB using homemade IB, due to its known clinical-therapeutic implications. Disclosure of interests: Ana Milena Millán arciniegas: None declared, M. ANGELES MARTINEZ: None declared, aNAIS MARISCAL: None declared, aNDRES BAUCELLS: None declared, Leticia alserawan: None declared, Ernesto Trallero: None declared, Cesar Díaz-Torné: None declared, ana Laiz Consultant for: Lilly, Novartis, abbVvie, MSD, UCB and Janssen, Speakers bureau: Lilly, Novartis, abvvie, MSD, UCB and Janssen, Berta Magallares: None declared, Patricia Moya: None declared, HyeSang Park: None declared, andrea García-Guillén: None declared, Sycille Jeria: None declared, DAVID LOBO: None declared, albert Gil: None declared, Coral Gozalvez: None declared, Susana P. Fernandez-Sanchez: None declared, Laura Martínez-Martínez: None declared, Esther Moga: None declared, Hector Corominas: None declared, Cándido Juarez: None declared, Ivan Castellví Consultant for: I received fees less than 5000USD as a consultant for Kern and actelion, Paid instructor for: I received fees less than 2000USD as a instructor for Boehringer -Ingelheim, Novartis and Gebro, Speakers bureau: ND, albert Selva-O'Callaghan: None declared